The Effect of Psycho-education Based Audiovisual Program on Behavior Adherence for Preventing Tuberculosis Transmission - Anita Dewi Anggraini; Soedarsono Soedarsono; Laily Hidayati (International Journal of Nursing and Health Services (IJNHS), 2020)
Treatment failure, disease transmission, and drug resistance were problems that occur due to non-compliance. One of the factors that caused non-compliance was a prolonged psychological problem and a lack of patient commitment to treatment. Psychoeducation, which was guided by implementation intention and packaged in audio-visual form, was expected to improve the behavior of adherence for preventing tuberculosis transmission. This study aims to explain the effect of psychoeducation based audio-visual programs on the behavior of adherence for preventing tuberculosis transmission. Methods: A quasi-experimental design, pre-test, and post-test with the equivalent control group were applied in this study. The study sample was 72 TB patients who underwent intensive category one treatment as many as two divided into two intervention groups (n=36) and controls (n=36). Samples were taken by random cluster sampling, inclusion criteria for intensive treatment category 1 TB patients (1-2 months), aged 18-65 years, and able to communicate verbally and in writing well. The behavior of preventing tuberculosis transmission was assessed using a questionnaire adapted from the Sukartini research in 2015. Data were analyzed using the Wilcoxon-Sign Rank test and the Mann-Whitney test. Results: After the intervention of psychoeducation based audio-visual programs, it was found that there was a significant increase in the behavior of adherence for preventing tuberculosis transmission in the intervention group with P<0.05. Conclusion: Psychoeducation based audio-visual program is an effective intervention to improve the behavior of adherence for preventing tuberculosis transmission